Review of Key Competencies in the Knowledge Society Conference 2010: E-Learning and Computer Competency Research in the Age of Social Media - Nycyk, Michael (Digital Culture & Education, 2011)
In September 2010, I attended the Key Competencies in the Knowledge Society(KCKS) conference, held as part of the International Federation for Information Processing World Computer Congress (WCC) in Brisbane, Australia. The WCC is held every two years in a host nation and was organised by the Australian Computer Society. The uniqueness of this conference is the mix of commercial and corporate sectors, non profit organisations, government departments, schools and academic researchers from many countries who present academic and commercial research. My key observation of the conference was that social media and technological devices are educational tools now becoming indispensable for learning and acquiring information and knowledge. With the large array of Web 2.0 tools currently in existence students are now authors of content in their learning (Gray et al., 2010). The issue of how to develop competent skills to use Web 2.0 tools in this fashion was the central concern of the researchers at the conference.